Combined application of biochar and sulfur regulated growth, physiological, antioxidant responses and Cr removal capacity of maize (Zea mays L.) in tannery polluted soils. (1st April 2020) - Bashir, Muhammad Asaad; Naveed, Muhammad; Ahmad, Zahoor; Gao, Bin; Mustafa, Adnan; Núñez-Delgado, Avelino
Abstract: Soil contamination due to heavy metals is a serious problem worldwide. Leather industry is one of the leading sectors in this regard in Pakistan, discharging heavy metal chromium (Cr) through untreated wastewater. In this study, effect of biochar and elemental sulfur (ES) were evaluated on maize growth, physiology, redox homeostasis and Cr dynamics in tannery polluted soils. Biochar was produced through pyrolysis of sugarcane bagasse at 350 °C and was applied at a rate of 3% (w/w) along with different rates of ES (3 and 6 g kg −1 soil). Results revealed that Cr toxicity in tannery polluted soils negatively affected plant growth, physiological and biochemical attributes. Reduction in plant growth and accumulation of Cr(III) and Cr(VI) in roots and shoots were higher in Sialkot (S) soil compared to Kasur (K) soil. Application of biochar and ES (6 g kg −1 ) resulted in maximum increase in plant height, biomass, chlorophyll content, photosynthesis, relative water, starch and protein content, as compared to control. While electrolyte leakage, soluble sugars, proline content, lipid peroxidation and antioxidant enzymes (APX, CAT, GSH, GR, GPX, GST and SOD) were decreased by addition of biochar and ES in tannery polluted soils. Similarly, combined application of biochar and ES decreased Cr concentrations in soil, and reduced uptake of Cr(VI) and Cr(III) concentration in roots and shoots of plants in S soil compared with K soil. In conclusion, application of biochar in combination with ES could be considered an interesting environmentally sound option for remediation of tannery polluted soils. Graphical abstract: Image 1 Highlights: Cr inhibited the plant growth, altered physiology and biochemistry of maize grown in tannery polluted soils. Application of sugarcane bagasse-derived biochar and elemental sulfur retrieved harmful effects of Cr in maize. Combined use of biochar and elemental sulfur (ES) mobilized Cr in soil and reduced uptake in plant. Productivity of tannery polluted soils could be restored by biochar and ES interaction.